Observation of PSAK 108 concerning to accounting of Sharia Insurance Transactions in Islamic Knowledge According to Yusuf Qardhawi: Observation of PSAK 108 concerning to accounting of Sharia Insurance Transactions in Islamic Knowledge According to Yusuf Qardhawi - Anggi, Anggita Muslihani; Andira, Ayu (UMBanjarmasin, 2022)
Life insurance is one of the institutes that plays an important role in Indonesia, because life insurance contains activities that play a role in getting protection from the risks of financial life which cannot be known as a result of someone's death. At present the development of the insurance business is getting better, so that most industries have also emerged. One of them is sharia-based life insurance. Due to the existence of sharia life insurance, the Indonesian accounting association issued PSAK No. 108 which contains the accounting of sharia insurance transactions for an accounting policy that is managed and the provision of insurance services. The preparation and presentation of the life insurance financial statements is in line with the growth of existing Islamic law, showing that the influence of local socio-cultural customs on the formation of Islamic law is very strong, which can be seen in the results of the ijtihad of the priests of the schools of thought. In Yusuf Qardhwani's fatwa regarding insurance which clearly forbids however, the idea of ​​insurance was not rejected by him on condition that the adjustment of the concept must be a sharia concept and Yusuf Qardhawani discussed insurance in his book al-halal waal-haram wial-Islam written by him in the 60's. Because the book presents a study of religious law that underlies and is needed by Muslims